Ethnomedicinal Survey of Plants used for Management of Inflammatory Diseases in Ringim Local Government, Jigawa State, Nigeria - Abba, Anas; Dogara, Abdulrahman Mahmoud (Ethnobotany Research and Applications, 2021)
Background: Physical trauma, unpleasant chemicals, or microbial infections produce inflammation, which is a typical defensive reaction to wounded tissue. It is the body's response to inactivate or eliminate invading pathogens, remove irritants, and prepare tissues for repair. Inflammation is called Kumburi by Hausa tribe of northern Nigeria. Minor or chronic inflammation is considered one of the major diseases affecting people all over the world. According to current estimates, almost 6 million people worldwide suffer from chronic inflammation. Nigeria has an abundance of biodiversity that has largely gone untapped, and it could be a source of new lead compounds for the treatment and control of inflammation. This research was aimed to documents and evaluate the traditional methods used for the management of inflammatory diseases in the Ringim Local Government Area of Jigawa State. Methods: Ethnobotanical study for the medicinal plants that are used in the management of inflammatory diseases were conducted between the periods of May, 2016 – May, 2018 in Ringim Local Government Area of Jigawa State. Indigenous medicinal plant information was gathered utilizing a scientifically organized questionnaire with the aid of respondents who were considered in traditional/alternative medicine. Purposive sampling was used. Results: In total, 47 medicinal plant species were discovered in the study, which was divided into 25 families and used for the treatment and management of inflammation. To avoid any misidentification, species having the same local name were not collected. With ten species, Leguminosae is the most common family. Only species with a minimum of 0.6 relative frequency of citations were reported quantitatively. The study recorded the highest used value at (0.07), the relative frequency of citation (0.9), and the fidelity level 90 %. Conclusion: Plants with medicinal potential are still the only way forward, as their acceptance and recognition spread over the globe. The current study found that residents of the Ringim local government had a good understanding of the therapeutic plant. Despite the advancement of modern medicine, locals continue to rely on traditional herbs for health treatment. Keywords: Ethnomedicine, Ethnopharmacology, Inflammation, Management, Plants, survey,